The potential of growing winter varieties of onion (Allium cepa L.) on the Hilly Land of Jeli, Kelantan - Nor Razanah Che Ibrahim (2018)
Onion is an essential spice of everyday cooking but Malaysia has been lagging behind in onion production. Almost 100% of onions are imported from foreign countries in lieu of RM 63 million per annum. Higher yield of onion can be achieved with optimum growth factors and suitable varieties. An attempt was therefore undertaken to select some onion varieties and their planting time in the aim to establish feasibility of growing onion on the highland of Jeli, Kelantan. In this study, 16 winter varieties of onion from India and Bangladesh were used. The seedlings varieties were raised in the seed trays before transferred to the well-prepared field at the age of 35 days. Data on plant height, leaves number, bulbs diameter and bulbs weight were collected. The grading of onion bulbs was also performed. The appropriate planting date of selected two varieties, N-53 and Ono 276, was discovered from the field experiments, following similar methodology as mentioned above. The quality of seeds produced from the selected varieties were tested in the laboratory by calculating their germination potentials. Pathogen causing the seedling disease of onion has been identified through laboratory study. From the first experiment on varietal screening, it was observed that five varieties performed well under the environmental condition of highland of Jeli. N-53 found to be good followed by Ono 276, BARI Piaz 5, Ono 277 and Ono 286. It produced the maximum plant height (45.16 cm), bulb diameter (57.83 mm), bulb weight (92.13 g), and the total yield (12.44 t/ha). In the second experiment, among 15 varieties, only varieties N-53 and Ono 276 were chosen to find out the best planting time within March to April, as this is the period with less rain. The analysis of variance (ANOVA) showed that the planting date had a significant effect towards all the parameters taken. Planting on 1st April produced the maximum bulb yield for both varieties (19.49 t/ha). Both varieties produced good quality seeds, having germination speed ranging from 13.58 to 14.88 per day out of 25 seeds, germination index ranged from 3.73 to 3.92, mean germination time ranged from 6.73 to 7.47 and T50 ranged from 2.50 to 2.86, respectively. The seedling fall off in the field was identified as damping off disease and the fungus was identified as genus Fusarium based on morphological and microscopic observation. The winter varieties, N-53 and Ono 276 show good potential for cultivating in the highland of Jeli and it can be planted in early April every year.